Paracoccidioidomycosis in a liver transplant recipient - Thais Carneiro Lima; Regis Otaviano Franca Bezerra; Luiz Tenório de Brito Siqueira; Marcos Roberto de Menezes; Claudia da Costa Leite; Gilda Porta; Giovanni Guido Cerri (Revista da Sociedade Brasileira de Medicina Tropical)
ABSTRACT Paracoccidioidomycosis is a granulomatous systemic mycosis that is endemic in Latin America; it is an extremely rare infection following solid organ transplantation. In this study, we describe the first report of disseminated paracoccidioidomycosis in a 3-year-old girl who underwent liver transplantation 2 years previously. The radiologic diagnosis and patient follow-up are described. In addition, we review the clinical evolution and treatment regimens for this infection.